Visual Representation Profile of Junior High School in Solving The Geometric Word Problem - Rohmatin, Dian Novita; Kurniati, Dian; Susanto; Yudianto, Arfan (Education, Science, and Technology International Conference, 2025)
Visual representation is essential to provide an aid for the student to understand geometry word problems. A proper representation can help them to recognize a context of the problem and ease to plan the appropriate strategy to solve this. This qualitative study therefore aims to describe the profile of visual representation in solving geometric word problems. The subjects of this study were 30 students of class 9A MTs Negeri 3 Mojokerto in the 2024/2025 academic year. The results of the study reveals that 4 students used accurate schematic representation, 15 students used inaccurate schematic representation, and 11 students used pictorial representation. Students whom used accurate schematic representation described objects carefully and paid attention on the size, location, and distance between objects. Meanwhile, students whom used inaccurate schematic representation described the objects and the distance between the two objects, but there were some imperfections such as depicting lines representing sunlight (including depicting non-straight, non-single lines with various directions, not touching objects, cutting objects, through the back of the building) and not comparable between one line segment and another. In the meantime, students with pictorial representation only made drawing objects in the form of buildings and trees, and only added 1 information about the distance between the two objects.